Analysis of the external doses received by workers involved in the mitigation of the Goiania radiological accident (Brazilian Journal of Radiation Sciences, 2018)
In 1987, after identification that a stolen head of a Cs-137 radiotherapy irradiator was violated, it starts, in Goiania, the screening of the involved persons, the decontamination and the collection of the radioactive waste. The contaminated areas were isolated and the professionals who worked within these areas received individual film monitors and TLD rings, provided by the Instituto de Radioproteção e Dosimetria of the Comissão Nacional de Energia Nuclear (IRD/CNEN), to evaluate their external dose. The aim of this paper is to present a statistical analysis of the external occupational doses received by this intervention staff. The used data were extracted from the Goiania accident database, maintained by IRD/CNEN. A total of 1091 workers were monitored, some for only a few days and others for almost one year. All the total external occupational doses, received during these works, including the management of the radioactive waste, were lower than the individual annual dose limit of 50 mSv for practices. Only one dose exceeded the value of 20 mSv. Their estimated mean effective doses were about 1.0 mSv, which is the annual dose limit for public exposure. About 80% of the doses were lower than this value. The measured extremity doses were even lower than the measured whole body doses values.